A Representation of Female Identity In Greta Gerwig's Barbie Movie (2023) - Rahmawati, Wina; Sembiring, Lina Tri Astuty Beru; Rullyanti, Merry (Amirul Bangun Bangsa Publishing, 2026)
This study discusses the representation of female identity through the main character Barbie in Greta Gerwig's film Barbie (2023). This study has two main objectives: (1) to analyze how female identity is represented through the character of Barbie; and (2) to explore how this film conveys social criticism of gender roles and female stereotypes. This study used a qualitative descriptive method with content analysis techniques. The data were collected from dialogues, visuals, and selected scenes in the film. The analysis was conducted using Stuart Hall's theory of representation, supported by feminist theory and concepts of female identity.The results of the study show that the character of Barbie undergoes a significant transformation from a perfect doll to an independent woman who questions societal standards, accepts imperfection, and determines her own identity. The film also presents strong social criticism of the patriarchal system and gender stereotypes through its narrative, visuals, and dialogue. Thus, Barbie (2023) serves not only as entertainment but also as a reflective medium that critiques the construction of women's identity in contemporary society.